Climate-Smart Agriculture Investment Plan for Mali - World Bank (2019)
This document provides an investment plan for climate-smart agriculture (CSA) in Mali, developed with support of the AAA Initiative and the World Bank, and technical assistanceof the International Center for Tropical Agriculture, the World Agroforestry Centre and the CGIAR Research Program on Agriculture, Climate Change and Food Security (CCAFS). It identifies specific interventions that define on-the-ground action that are consistent with Mali’s NDC and national agricultural strategy, which can be funded by public and private sector partners. CSA interventions are designed to increase agricultural productivity, to help farmers, livestock keepers and fisher-people adapt and build resilience to climate risks, and, where appropriate, to reduce greenhouse gas emissions that cause climate change.This plan includes a set of 12 key CSA investments for Mali that were developed with strong stakeholder engagement, expert input and scientific evidence. This plan is not intended to be comprehensive but can further include additional projects when more funds will be available. The plan presents a situation analysis of Mali’s national policies, plans and programs in relation to key climate risks, which form the context for key prioritized interventions. Designed project concepts are developed for each of these key investments, including the main project objectives, components and implementation arrangements. These provide a tangible set of project concepts for potential investors and donors to consider for funding. Finally, a general framing for developing a monitoring and evaluation (M&E) framework for the CSA investment plan (CSAIP) is provided, showing how CSA outcomes relate to other M&E frameworks and other monitoring activities for national-level development priorities.The CSAIP provides the context and evidence for the importance of these projects, and details how they can be economically beneficial and provide food security to the people of Mali. This can help spur investment and funding for CSA to help Mali deliver on its NDC and other national targets